2020
DOI: 10.1186/s40364-020-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased PD-1+Tim-3+ exhausted T cells in bone marrow may influence the clinical outcome of patients with AML

Abstract: Background: Altered expression of T cell immune inhibitory receptors may result in immunosuppression and associate with the poor prognosis of leukemia patients in which the leukemic bone marrow (BM) microenvironment may contribute to such immunosuppression. We found higher numbers of programmed death-1 (PD-1) + exhausted T cells in peripheral blood (PB) from acute myeloid leukemia (AML) patients. To investigate the leukemic BM influence on immunosuppression, we further compared the distributions of PD-1 and T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 34 publications
0
62
1
Order By: Relevance
“…Although TIGIT expression had no effects on CD8 + T cells, it was associated with impaired cytokine production ability of CD4 + T cells in patients with CLL. Despite previous reports on the important role of TIM-3 and Gal-9 interactions in T cell exhaustion in hematological and non-hematological cancers, 60 61 we observed a very low expression level of these co-inhibitory receptor/ligand in T cells of patients with CLL.…”
Section: Discussioncontrasting
confidence: 99%
“…Although TIGIT expression had no effects on CD8 + T cells, it was associated with impaired cytokine production ability of CD4 + T cells in patients with CLL. Despite previous reports on the important role of TIM-3 and Gal-9 interactions in T cell exhaustion in hematological and non-hematological cancers, 60 61 we observed a very low expression level of these co-inhibitory receptor/ligand in T cells of patients with CLL.…”
Section: Discussioncontrasting
confidence: 99%
“…Periphery blood (PB) samples of AML patients showed us the immune dysfunction of lymphocytes based on the analysis of flow cytometry and immune-related risk of factors, indicated that the immune signatures corrected clinical outcomes [ 36 ]. The immune status of BM microenvironment are more sensitive to reflect immune response for clearing AML blast cells compared to PB [ 37 ]. So dissecting the immune landscape of AML is important for predicting the immune status and screening suitable immunoregulatory drugs.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that T cells with the exhausted and suppressive phenotype may have reduced activation and be related to poor prognosis for AML patients [21,22]. Elucidation of the role of TIGIT on γδ Tregs in this context may assist in understanding the dysfunctional immunobiology of γδ cells in AML patients of different clinical statuses.…”
Section: Discussionmentioning
confidence: 99%